The Effects of Peer-Controlled or Moderated Online Collaboration on Group Problem Solving and Related Attitudes - Ke Zhang; Kyle Peck (The Canadian Network for Innovation in Education (CNIE), 2003)
Abstract. This study investigated the relative benefits of peer-controlled and moderated online collaboration during group problem solving. Thirty-five self-selected groups of four or five students were randomly assigned to the two conditions, which used the same online collaborative tool to solve twelve problem scenarios in an undergraduate statistics course. A score for the correctness of the solutions and a reasoning score were analyzed. A survey was administered to reveal differences in students' related attitudes. Three conclusions were reached: 1. Groups assigned to moderated forums displayed significantly higher reasoning scores than those in the peer-controlled condition, but the moderation did not affect correctness of solutions. 2. Students in the moderated forums reported being more likely to choose to use an optional online forum for future collaborations. 3. Students who reported having no difficulty during collaboration reported being more likely to choose to use an optional online forum in the future.